Development of Performance Assessment Instruments to Measure Students’ Scientific Thinking Skill in the Quantitative Analysis of Acetic Acid Levels - Firmansyah, Dea Rian; Nahadi, Nahadi; Firman, Harry (FKIP - Universitas Riau, 2020)
This study aims to develop good quality performance assessment instrument that can be used to measure students’ scientific thinking skills. The research method used is Development & validation The study describes the 5 stages of instrument development, namely the analysis of performance assessment journals, analysis of Core Competency and Basic Competency on 2013 curriculum, field surveys, development of indicators and student worksheets, as well as target skills and rubric development. The developed instrument consists of 33 target skills (experimental problem solving) and 9 target skills (quantitative literacy). The expected value in this research is the accuracy of students in performing practical work. In the validity test, it is obtained a CVR value of 1.00 on 42 developed target skills, so that the instrument was declared as valid. Based on the analysis of research data, it can be concluded that the developed performance assessment instruments have good quality to measure students' scientific thinking skills.